In-situ cleaning of heavy metal contaminated plastic water pipes using a biomass derived ligand. Issue 4 (August 2017) - Huang, Xiangning; Zhao, Shou; Abu-Omar, Mahdi; Whelton, Andrew J.
Graphical abstract: Highlights: A biomass derived ligand was synthesized and examined as a pipe cleaning agent. Heavy metal loading on exhumed plastic water pipes was quantified. 95% of sorbed heavy metals were removed at low ligand concentration. The ligand was selective for Zn and Cu compared to Fe, Mn and Pb. Abstract: Lignin derived monomer (2-methoxy-4-propylphenol, Dihydroeugenol, DHE) was used to synthesize a biomass based plumbing pipe cleaning agent (DHEL). DHEL's metal deposit removal efficiency for an exhumed plastic drinking water pipe was examined. The total metal deposited on 3 cm pipe segments was first characterized and heterogeneous metal loading (μg/dm 2 ) along consecutive pipe segments was found. Fe was the most abundant metal species detected, followed by Mn, Ca, Zn, Mg, Cu, Pb and Al. Both DHEL metal removal kinetic and performance studies (0.1 to 10 mM) were conducted at room temperature and neutral pH for up to 7 days. Results showed DHEL effectively removed metal deposits from exhumed plastic pipe surfaces. By the end of the experiment,  ≥ 95% of total metal loadings were removed when DHEL dosage was ≥ 5 mM. Both first order and second order kinetic models were used to fit the experimental data. DHEL showed higher favorability for Cu and Zn rather than Fe, Mn, and Pb. DHEL-metal removal mechanisms were proposed as: 1) ligand-promoted minerals dissolution, and 2) ligand-metal complex formation. The biomass derived ligand demonstrated potential as an effective plastic pipe cleaning agent.